2014
DOI: 10.1136/bjsports-2014-094036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-rich plasma injections in osteoarthritis of the knee: a systematic review and meta-analysis

Abstract: BackgroundThe effectiveness of platelet-rich plasma (PRP) injections for osteoarthritis (OA) is still controversial. We investigated the effect of PRP injections in patients with knee OA based on decreasing pain, improving function, global assessment and changes regarding joint imaging. Methods We performed a comprehensive, systematic literature search in computerised databases (MEDLINE, EMBASE, CINAHL, CENTRAL, Web of Science and PEDro) until June 2014 for randomised or nonrandomised controlled trials. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
230
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(256 citation statements)
references
References 49 publications
10
230
0
16
Order By: Relevance
“…Having failed non-operative treatment modalities, in three-quarters of cases their pain and functional scores are the same, if not worse than patients with more advanced structural changes 2 . In randomised studies arthroscopy has been shown not to help this group of patients and there is uncertainty over the role of nonoperative treatments including the use of corticosteroids, hyaluronic acid and platelet rich plasma [3][4][5][6] . As such these patients represent a significant clinical challenge and the optimum treatment of this group, including the role of expectant management, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Having failed non-operative treatment modalities, in three-quarters of cases their pain and functional scores are the same, if not worse than patients with more advanced structural changes 2 . In randomised studies arthroscopy has been shown not to help this group of patients and there is uncertainty over the role of nonoperative treatments including the use of corticosteroids, hyaluronic acid and platelet rich plasma [3][4][5][6] . As such these patients represent a significant clinical challenge and the optimum treatment of this group, including the role of expectant management, is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Diversi studi mostrano che il PRP ha un'efficacia superiore all'HA (34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Discussioneunclassified
“…Так, A. Laudy и соавт. [68] изучили данные 10 РКИ, в которых проводилось сравнение эффекта внутрисустав-ного введения ОТП, гиалуроновой кислоты (ГРК) и плаце-бо. В сравнении с физиологическим раствором, активный препарат обеспечивал достоверно лучшее уменьшение бо-ли: через 6 мес среднее отличие составляло -2,45 (95% ДИ от -2,92 до -1,98; p<0,00001) и -2,07 (95% ДИ от -2,59 до -1,55; p<0,00001) для однократной и повторных инъекций.…”
Section: обогащенная тромбоцитами плазмаunclassified